Evaluation of safe exposure time for two-photon microscopy imaging of acrylic-painted mock-ups - Sara Mattana; Alice Dal Fovo; Enrico Baria; Raffaella Fontana; Riccardo Cicchi (JPhys Photonics)
Nonlinear optical microscopies are widely used in the biological and biomedical fields, as they are non-invasive techniques that permit the safe structural and morphological characterisation of cells and tissues. They are increasingly being used in the Cultural Heritage field because of their ability to overcome some limits of the well-established optical techniques. However, since nonlinear optical microscopies use pulsed laser sources with high peak power, their application in Cultural Heritage raises concerns due to artworks’ unique, priceless, and delicate nature. In this paper, we present a new method for evaluating the photo-induced damage when using a near-infrared femtosecond pulsed laser to perform two-photon excited fluorescence imaging of acrylic-painted mock-ups. In particular, we explore herein several irradiation conditions, varying the exposure time and excitation power, in order to provide useful experimental indications for safely imaging acrylic paints with two-photon microscopy.